Ijtihad Nahdlatul Ulama - Irdlon Sahil (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Abstract: Lajnah Bahtsul Masail NU is the agency which is in charge to solve fiqhiyyah problems that occur among NU members. In solving religious issues, qauliy ijtihad is still being used, it is a method of ijtihad in istinbat method to study the problems faced, then looking for the answers in the fiqh books from the four madzhabs, by directly referring and to the sound of the text. If the qauliy method can not be implemented because the texts from kutub muktarabah from the four madzhabs were not found, then by using what is so called ilhaqiy method, that is Ø§Ù„ØØ§Ù‚ Ø§Ù„Ù…Ø³Ø§Ø¦Ù„ Ø¨Ù†Ø¸Ø¦Ø±Ù‡Ø§ (equating the law of a case that has not been answered by the book with a case that has been answered by the book ). Manhajiy method is a way of solving religious problem which was reached by following the mind path and determined norm of law that has been drafted by the madzhab imam, this method is used by the intellectual NU when both of the abovementioned methods cannot be implemented.